TOXIC EFFECTS OF THE CONTENTS OF TWO CYST SIZES OF SARCOCYSTYS AUCHENIAE IN EXPERIMENTALLY INOCULATED RABBITS - Chileno M., María (2011)
The aim of this study was to determine the toxic effects of two macrocyst sizes of Sarcocystis aucheniae (>5 mm and 1-3 mm) in experimentally inoculated rabbits through survival time, clinical signs, and pathological changes. Macrocysts from alpaca necks were collected in the slaughterhouse of Huancavelica, Peru. Antigenic proteins concentrations from large and small macrocysts, measured by the Biuret method were 3.3 and 2.4 mg/mL, respectively. Twenty five rabbits were inoculated with extracts from large macrocysts, 25 with extracts from small macrocysts and 2 animals were used as controls. Each treatment group was formed by 5 subgroups of 5 rabbits each, which received, via IM, doses of 2.5, 5, 10, 15, and 25 ?g of protein per kg of body weight. Survival time was evaluated until 72 hours post inoculation. The average interval to death was 7 h and the more severe lethal dose was 15 ?g/kg. The most frequent clinical signs were hyperthermia, tachypnea, diarrhea, inappetence, incoordination, and recumbency. The principal lesion at necropsy was congestion of blood vessels in brain and other organs, and fluid in the abdominal, thoracic, and pericardial cavities. Also, degenerative lesions in brain, liver and kidney as well as brain oedema were found. Changes in skeletal muscle were not observed. The severity of injuries was related to size cyst, being worse with small cysts. Statistical difference (p<0.05) in survival time due to the effect of dose and size of macrocyst was found. There were 96% survival for animals inoculated with large macrocysts and 68% for those inoculated with small macrocysts.